2018
DOI: 10.3390/f9040191
|View full text |Cite
|
Sign up to set email alerts
|

Downed Coarse Woody Debris Dynamics in Ash (Fraxinus spp.) Stands Invaded by Emerald Ash Borer (Agrilus planipennis Fairmaire)

Abstract: Emerald ash borer (EAB; Agrilus planipennis Fairmaire) has had major ecological impacts in forests of eastern North America. In 2008 and 2012, we characterized dynamics of downed coarse woody debris (DCWD) in southeastern Michigan, USA near the epicenter of the invasion, where the mortality of white (Fraxinus americana L.), green (F. pennsylvanica Marshall), and black (F. nigra Marshall) ash exceeded 99% by 2009. Percentage of fallen dead ash trees and volume of ash DCWD on the forest floor increased by 76% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…The resulting influx of detritus can affect stand development processes for decades in some locations [13]. However, a changing climate is not the only factor leading to recent increases in tree mortality: Invasions of diseases such as sudden oak disease (Phytophthora ramorum) [14] and insects such as the emerald ash borer (Agrilus planipennis) [15,16] and hemlock woolly adelgid (Adelges tsugae) [17] are causing wide spread mortality of their new host tree species. Moreover, there is increasing evidence that small scale mortality (i.e., so-called regular or background mortality) has been increasing in western North America [18,19] and southern Europe [11].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting influx of detritus can affect stand development processes for decades in some locations [13]. However, a changing climate is not the only factor leading to recent increases in tree mortality: Invasions of diseases such as sudden oak disease (Phytophthora ramorum) [14] and insects such as the emerald ash borer (Agrilus planipennis) [15,16] and hemlock woolly adelgid (Adelges tsugae) [17] are causing wide spread mortality of their new host tree species. Moreover, there is increasing evidence that small scale mortality (i.e., so-called regular or background mortality) has been increasing in western North America [18,19] and southern Europe [11].…”
Section: Introductionmentioning
confidence: 99%
“…Individual gaps from EAB-induced ash mortality are relatively small because most ash species exist in diverse forest communities . The speed, synchrony, and specificity of EAB-induced ash mortality make it a unique phenomenon in eastern North America [91,96,97], and warrant a focus on the indirect effects of ash mortality on ground-dwelling invertebrate communities.…”
Section: Responses Of Ground-dwelling Invertebrates To Patterns Ofmentioning
confidence: 99%
“…Ash mortality caused by EAB increases the frequency of gaps in the canopy and ash CWD on the forest floor [35,91,97]. For invasive insects, such as EAB, an inverse temporal relationship is predicted for the effect sizes of canopy gaps and accumulation of CWD on ground-dwelling invertebrate communities (Figure 1).…”
Section: Responses Of Ground-dwelling Invertebrates To Patterns Ofmentioning
confidence: 99%
“…Impacts of CWD, in contrast, are predicted to increase over time [76] as ash trees die, standing snags fall, and CWD accumulates and decomposes on the forest floor. For example, Higham et al [74] observed rapid accumulation of CWD across a chronosequence of ash mortality in Ohio, and in the Upper Huron River watershed, the number of fallen ash trees increased by 76% from 2008-2012, and volume of ash CWD increased by 53% [77].…”
Section: Ground-dwelling Invertebratesmentioning
confidence: 99%